Pengaruh Biaya Bahan Baku, Tenaga Kerja Langsung dan Overhead Pabrik terhadap Harga Pokok Produksi dengan Inflasi Sebagai Variabel Moderasi : Study Perusahaan Sektor Kosmetik Yang Terdaftar Di Bursa Efek Indonesia Periode 2016- 2021 - Suswandoyo, M. Imam; Saputri, Dinah (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To analyze in a Company the Cost of raw materials, direct labor, factory overhead costs and COGS due to inflation. Background Problems: The cost of raw materials, direct labor, factory overhead costs and COGS experienced different increases and decreases or fluctuated from 2016 to 2020. Novelty: Re-testing previous research on different companies and research times. Research. Research Methods: Using a quantitative descriptive method with SPSS as a tool in measuring the variables studied and using several methods in its testing. Finding/Results: That the cost of raw materials and direct labor has a positive effect on the cost of production. Meanwhile, factory overhead costs do not have a significant effect on the cost of production. Conclusion: Can provide input for companies in managing production costs and taking into account inflation factors in planning and controlling production costs.